NAO with vision algorithm - Seet, Dai Sheng (2017)
Automation serves as a technology to improve our daily life. With such technology, we will be able to replace hard manual labours and make work easier and faster. In other terms, to increase efficiency and productivity. This has been implemented in both workplaces and home applications. The importance of home automation is becoming more familiar as technologies evolve. The NAO robot was designed to be programmable with a wide variety of performances. It is a very useful tool to enhance learning of programming for home applications. In this report, the aim is to explore and discover the different ways exploited in the NAO robot. It will explain the theoretical method and background study of these functions. There will then be a further discussion on future development and improvement that can enhance productivity and make things easier in daily routine work.